JUSTIFICATION OF SCIENTIFIC FOUNDATIONS AND RESEARCH DIRECTIONS FOR IMPROVING THE LINTERING MACHINE FOR HAIRED SEEDS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article provides an analytical review of scientific research results regarding the process of depilation of cotton seeds and the improvement of related equipment. Additionally, a working hypothesis was put forward and a scientific research direction was defined to increase the productivity and improve the energy efficiency of the 5LP linter.